A Value chain analysis of Sesame (Sesame Indicum L.) in South Omo Zone, Southern Ethiopia - Kusse, Kutoya; Ermias, Gedion; Darcho, Dawit (Applied Studies in Agribusiness and Commerce, 2022)
Sesame is the main cash crop in Ethiopia and it is mainly produced in northern and southern part of the country especially South Omo Zone. In the zone sesame is highly produced, but it production is not known regionally and at a country level. So this study was aimed to research sesame value chain of the Zone. Simple descriptive statistics and value chain approach were employed for data analysis during this study. It attempts to deal with mapping and identifying sesame value chain actors and their roles, examines marketing channel, cost margin structure and assessing challenges and opportunities within the study area. The results of the study indicated that out 5589.3 quintals were supplied to markets for various actors and five alternative marketing channels were identified to transact the sesame product through intermediaries. The most important volume of sesame (4900.8 quintals) was marketed through channel V and the lowest volume in channel I. producers get the highest share in channel IV and the lowest in channel II. Barriers to entry traders into the market are that the capital requirement and therefore the wholesalers govern by volume transacted and internal control criteria within the market. Fertile land and high demand for the product were essential opportunity. Pests and disease, Low level of input utilization, Shortage of input supply and high price of inputs were the challenges of sesame production whereas lack of market information, price variability, delay of buyers, low bargaining power and poor product quality were the challenges sesame marketing.